SYNTHESIS OF NANOCRYSTALLINE COMPLEX OXIDES IN SUPERCRITICAL ALCOHOLS - Altynbekova Dinara Tancikovna,; Massalimova Bakytgul Kabykenovna,; Bespalko Yulia Nikolaevna,; Valeev Konstantin Radikovich,; Krieger T.A.,; Sadykov Vladislav Aleksandrovich, (Academic Scientific Journal of Chemistry, 2020)
An intensive search for solid electrolytes with high proton conductivity is being continued over the past few decades, which is primarily due to the high practical significance of these systems. Proton conductors are widely used as components of electrochemical devices such as gas sensors, electrolyzers, fuel cell membranes, etc. The variety of currently known solid proton conductors can be classified by operating temperature parameters, with the allocation of low, medium and high temperature regions. Each class, from the point of view of its practical use, has a number of advantages, but at the same time, specific disadvantages that hinder practical implementation. In this regard, the material science goal - the synthesis of new materials with functional properties, remains relevant. For the first time, complex oxides – lanthanum niobates – were synthesized using alcohol solutions of salts of the corresponding metals by the solvothermal method in a flow reactor in a supercritical isopropanol medium. This method allows one to obtain single-phase lanthanum orthioniobate oxides, the phase composition, structure and morphology of which is characterized by X-ray phase analysis (XRD), Raman spectroscopy (Raman spectroscopy), scanning and transmission electron microscopy (SEM and TEM).